Diagnosis and classification of disorders specifically associated with stress: proposals for ICD‐11. Issue 3 (4th October 2013) - Maercker, Andreas; Brewin, Chris R.; Bryant, Richard A.; Cloitre, Marylene; van Ommeren, Mark; Jones, Lynne M.; Humayan, Asma; Kagee, Ashraf; Llosa, Augusto E.; Rousseau, Cécile; Somasundaram, Daya J.; Souza, Renato; et al.
Abstract : The diagnostic concepts of post‐traumatic stress disorder (PTSD) and other disorders specifically associated with stress have been intensively discussed among neuro‐ and social scientists, clinicians, epidemiologists, public health planners and humanitarian aid workers around the world. PTSD and adjustment disorder are among the most widely used diagnoses in mental health care worldwide. This paper describes proposals that aim to maximize clinical utility for the classification and grouping of disorders specifically associated with stress in the forthcoming 11th revision of the International Classification of Diseases (ICD‐11). Proposals include a narrower concept for PTSD that does not allow the diagnosis to be made based entirely on non‐specific symptoms; a new complex PTSD category that comprises three clusters of intra‐ and interpersonal symptoms in addition to core PTSD symptoms; a new diagnosis of prolonged grief disorder, used to describe patients that undergo an intensely painful, disabling, and abnormally persistent response to bereavement; a major revision of "adjustment disorder" involving increased specification of symptoms; and a conceptualization of "acute stress reaction" as a normal phenomenon that still may require clinical intervention. These proposals were developed with specific considerations given to clinical utility and global applicability in both low‐ and high‐income countries.